2018
DOI: 10.1111/ppe.12465
|View full text |Cite
|
Sign up to set email alerts
|

Association between prenatal psychological stress and oxidative stress during pregnancy

Abstract: These data suggest that 8-iso-PGF is elevated in pregnant women with who are at a sociodemographic disadvantage and who have higher psychological stress in pregnancy. Previous studies have observed that 8-iso-PGF levels are associated with adverse birth outcomes, oxidative stress could be a mediator in these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 35 publications
(75 reference statements)
1
38
0
Order By: Relevance
“…Our final model was a priori adjusted for maternal education (�college degree yes/no), maternal race/ethnicity (non-Hispanic white yes/no), and maternal age at enrollment. These variables were chosen based on their known associations with psychosocial stressors during pregnancy [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our final model was a priori adjusted for maternal education (�college degree yes/no), maternal race/ethnicity (non-Hispanic white yes/no), and maternal age at enrollment. These variables were chosen based on their known associations with psychosocial stressors during pregnancy [9].…”
Section: Resultsmentioning
confidence: 99%
“…Psychosocial stress and responses to stress during pregnancy may contribute to the persistence of disparities in adverse birth outcomes across socioeconomic and racial and ethnic groups. For example, research from a multi-center pregnancy cohort indicated that roughly 50% of women with less than a college degree reported experiencing at least one stressful life event during pregnancy, compared to only 33% of women who had completed college [9]. However, stressful life events were not associated with preterm birth in that cohort [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between the oxidative stress biomarkers and demographic characteristics are presented in Supplemental Table 3 and have been previously discussed for this study population. 23 Adjusted associations between the three measured urinary oxidative stress biomarkers and urinary phthalate and DINCH metabolites are presented in Table 4. All phthalates metabolites except for MEP had significant positive associations with 8-iso-PGF 2α .…”
Section: Resultsmentioning
confidence: 99%
“…It is hypothesized that psychosocial stress contributes to PTB through activation of the hypothalamic-pituitary-adrenal (HPA) axis, which increases cortisol production [5]. Psychosocial stress may also increase oxidative stress and inflammation, which are increased in mothers who go on to experience PTB [5,[31][32][33]. Additionally, psychosocial stress may lead to unhealthy behaviors, such as smoking or poor nutrition, which may increase the risk of PTB through these or other pathways [5].…”
Section: Discussionmentioning
confidence: 99%